The Current Status of Green Residential Projects in Tier-II Cities of India - Jain, Anshul; Babu , Ananda (Urban Planning and Construction, 2025)
Green residential projects, defined by sustainable design, energy efficiency, and reduced environmental impact, are gaining traction in India’s rapidly urbanizing Tier-II cities, such as Coimbatore, Jaipur, and Chandigarh. These cities are emerging as hubs for green development, propelled by government initiatives like AMRUT, consumer demand for eco-friendly living, and developer incentives. This research paper evaluates the adoption, implementation, benefits, and challenges of green residential projects in these cities, using case studies from Jaipur and Coimbatore. Drawing on data from the Indian Green Building Council (IGBC), government reports, and stakeholder interviews, the study reveals that 18% of new residential projects in Tier-II cities are green-certified, achieving a 30% reduction in energy consumption and a 20% increase in property value. These projects incorporate sustainable features like solar panels, rainwater harvesting, and energy-efficient materials, aligning with India’s sustainability goals for 2030. However, challenges such as high initial costs, limited public awareness, and inconsistent regulatory frameworks impede broader adoption. The case studies highlight successful implementations but also underscore the need for localized solutions. The paper proposes actionable strategies to scale green residential projects, including enhanced policy incentives, targeted public awareness campaigns, and technological innovations like AI-driven energy management systems. By addressing these barriers, Tier-II cities can lead India’s transition to sustainable urban living, setting a precedent for other states to incentivize green residential development and contribute to national environmental targets by 2030.